Students' Voices on the Use of Canva-Based Interactive Animated Video for Descriptive Text Writing Skills - Rahayu, Wa; Dzulfikri, Dzulfikri; Karimullah, Imam Wahyudi; Subarjo, Subarjo; Ramadani, Fitra (Universitas Cokroaminoto Palopo, 2026)
This study investigates students’ voices on the use of Canva-based interactive animated video in developing descriptive text writing skills. Conducted with seventh-grade students at SMPN 18 Malang, the research adopts a qualitative exploratory design using semi-structured interviews and classroom observations to capture learners’ perceptions and experiences. Findings are organized into three themes: students’ responses to the introduction of interactive animated video, the influence of Canva-based media on their engagement with descriptive writing, and insights into the broader role of digital media in shaping writing practices. Results reveal that interactive animated video provides clarity, motivation, and confidence, transforming writing from a rigid, rule-based activity into an engaging and creative process. Students reported that the integration of multimedia elements enhanced their focus, encouraged active participation, and fostered creativity and collaboration. The study concludes that Canva-based interactive animated video serves as an effective pedagogical tool for supporting descriptive writing instruction, while also highlighting the need for future research to explore diverse contexts, longitudinal impacts, and teachers’ perspectives on digital media integration.